STUDENTS’ PERCEPTION OF THE EFFECTIVENESS OF USING GOOGLE CLASSROOM APPLICATION AS AN INTEGRATION OF DISTANCE LEARNING TECHNOLOGY - Annisa Putri Octaviani; Ine Rahayu Purnamaningsih (Academy of Education Journal, 2023)
Distance learning during a pandemic like this is enough to make it difficult for some students to participate in learning activities. Google Classroom is an application that can be used as distance learning. Therefore, this study aims to obtain an overview of students’ perceptions of the effectiveness of using the Google Classroom application as an integration of distance learning technology. This research uses a qualitative method. With data collection techniques based on observations, interviews and filling out forms. With involving 30 students who have or are currently using the Google Classroom application as an integration of distance learning technology. The result of the study show that: (1) Students already have the basic facilities needed to participate in distance learning; (2) Distance learning using the Google Classroom application has flexibility in its implementation and is able to create independent learning and motivation to be more active in learning.